DINASTI TURKI USMANI - Muhammad Asra; Dewi Suci Cahyani Yusuf (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
Ottoman Turks is one of the kingdoms established by the Turks after the collapse of the Turkish kingdom of Saljuq. Entogrol was the entourage of the founding way of Turkey Usmani his son Usman as the proclamator of the Ottoman Empire of the year 1300M. The success of the Islamic empire in Turkey was during the Ottoman Dynasty, more precisely during the reign of Sultan Muhammad Al-Fatih in 1453 M. The decline and destruction of Ottoman Turks caused by several factors among others: the sultan's weakness and bureaucratic system, economic downturn and the emergence of strength Europe. In 1342 H / 1923 M khilafah Islamiyah was abolished, then Turkey changed to a secular republic. Mustafa Kemal in his reformation reform in realizing Modern Turkey brought ideologies of his Kemal such as Republicanism, Populism, Nationalism, Reformism, Secularism, and Ethism.